Supporting students with Tourette syndrome in secondary school: a survey of staff views - Wadman, Ruth; Glazebrook, Cris; Parkes, Emma; Jackson, Georgina M. (Wiley, 2014)
Tourette syndrome is a neurological condition involving involuntary movements and sounds (tics) and is thought to affect as many as 1% of school aged children. Some young people with Tourette syndrome experience educational difficulties and social difficulties. Current clinical guidelines suggest educators can play an important role in maximising learning potential and reducing the negative impact of this condition on students’ social adjustment. Secondary school staff (N = 63) with responsibilities for special educational needs or disabilities completed a survey about support strategies for students with Tourette syndrome. Participants were first asked to suggest potentially helpful strategies and then rated how easily 17 recommended strategies could be implemented in school. The survey participants suggested a range of support strategies that were categorised as (1) promoting knowledge and understanding in school, (2) helping the student to cope with his/her tics, (3) supporting the student’s learning and (4) providing social and emotional support. All the recommended support strategies were rated as being easy to implement (or already in place) by the majority of respondents (e.g., increasing staff awareness and regular communication with home). The strategies that were identified as being least easy to implement were those requiring extra staff input (support from teaching assistants and individual/small group working). Additional challenges to providing support were also identified by the participants (e.g., getting input from outside agencies).